2011
DOI: 10.1155/2011/841214
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Internal Flow in a Banki Turbine

Abstract: The paper refers to the numerical analysis of the internal flow in a hydraulic cross-flow turbine type Banki. A 3D-CFD steady state flow simulation has been performed using ANSYS CFX codes. The simulation includes nozzle, runner, shaft, and casing. The turbine has a specific speed of 63 (metric units), an outside runner diameter of 294 mm. Simulations were carried out using a water-air free surface model and k-εturbulence model. The objectives of this study were to analyze the velocity and pressure fields of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 9 publications
8
47
0
3
Order By: Relevance
“…Fiuzat and Akerkar [9] and De Andrade et al [11] have shown that the water flow within the impeller still possesses an appreciable energy content when it reaches the blade output (the energy at the blade output is 25%-35% of the energy at the inlet blades), where there is a second energy transfer from the water flow to the turbine.…”
Section: The State Of the Art On Michell-banki Parameter Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Fiuzat and Akerkar [9] and De Andrade et al [11] have shown that the water flow within the impeller still possesses an appreciable energy content when it reaches the blade output (the energy at the blade output is 25%-35% of the energy at the inlet blades), where there is a second energy transfer from the water flow to the turbine.…”
Section: The State Of the Art On Michell-banki Parameter Designmentioning
confidence: 99%
“…We will show in the following section that Equation (3) is equivalent to Equation (2) when the velocity of the rotating system is half of the component of the particle velocity in the tangent direction. Many researchers agree that the optimum value of β 2 is π/2 [10][11][12][13]. This value provides a radial direction to the relative outlet velocity inside the impeller at the inner diameter (D 2 ), and this leaves to the fluid, in the inner part of the impeller, only the energy of the rotating system, which can be recovered during the next blade crossing.…”
Section: The State Of the Art On Michell-banki Parameter Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The undershot cross-flow water turbine used by this study differs from cross-flow water turbines [6,7,10,11] for use with penstocks. Since there is no casing covering the runner, the interface between the water and air changes, particularly at the inlet and outlet regions of the runner.…”
Section: Comparison Of the Flow Fieldsmentioning
confidence: 99%
“…Therefore, it is necessary to clarify the complicated flow fields involving free surfaces in order to design water turbines of high efficiency and high rotational speed for use in open channels. With the development of computational fluid dynamics technology, the flow fields involved with various water turbine designs, such as a cross-flow water turbine [6,7] for use with penstocks and a spiral water turbine [8,9] for use in open channels, have been investigated by numerical analysis. However, the treatment of a flow field involving a free surface must efficiently and correctly capture the interface between the fluids of water and air.…”
Section: Introductionmentioning
confidence: 99%